1998
DOI: 10.1007/s002590050337
|View full text |Cite
|
Sign up to set email alerts
|

Role of nuclear medicine in melanoma

Abstract: Melanoma is a malignant tumour of the melanocytes presenting characteristic metabolic and biological features, which remains a difficult and important issue in oncology. As a functional modality, nuclear medicine offers a variety of possibilities to assist in the clinical management of this disease. A brief survey of currently available techniques is presented for the diagnosis, staging and follow up, either by organ imaging or by using a great spectrum of tumour-seeking radiopharmaceuticals. The role of lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The significant mortality of this cancer is associated with its high cellular proliferation rate and the early occurrence of metastases. Because early detection of the melanoma and its associated metastases considerably improves management and prognosis of the disease, there has been intense interest in the search for melanoma-specific diagnostic imaging probes and therapeutic agents (4,5 (6). Other prospective clinical studies have also shown the utility of whole-body [ 18 F]FDG PET imaging in stage II to IV melanoma with sensitivity and specificity of 94.2% and 83.3%, respectively, for lesions in the soft tissue, lymph nodes, and liver (7); false-positives are due to the accumulation of [ 18 F]FDG in surgical wounds, pneumonia, and other etiologies including infection/ inflammation (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant mortality of this cancer is associated with its high cellular proliferation rate and the early occurrence of metastases. Because early detection of the melanoma and its associated metastases considerably improves management and prognosis of the disease, there has been intense interest in the search for melanoma-specific diagnostic imaging probes and therapeutic agents (4,5 (6). Other prospective clinical studies have also shown the utility of whole-body [ 18 F]FDG PET imaging in stage II to IV melanoma with sensitivity and specificity of 94.2% and 83.3%, respectively, for lesions in the soft tissue, lymph nodes, and liver (7); false-positives are due to the accumulation of [ 18 F]FDG in surgical wounds, pneumonia, and other etiologies including infection/ inflammation (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…A number of radiolabeled, single-photon emission computed tomography (SPECT) metabolic tracers, peptides, and monoclonal antibodies have also been investigated for melanoma detection, staging, and follow-up (4,5). Among these SPECT agents, the most promising are the radioiodinated benzamides (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been renewed interest in the role of nuclear medicine in the management of patients with malignant melanoma [1]. The introduction of lymphoscintigraphy and sentinel node mapping has revolutionized the surgical treatment of this condition [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, attention has again focussed on the development of melanoma-specific radiopharmaceuticals. In contrast to more conventional diagnostic imaging techniques, such as chest X-ray, ultrasound, computed tomography (CT) scan, or magnetic resonance imaging, which only provide anatomical identification of metastatic deposits, these tracers permit tumor characterization by exploiting metabolic and biological properties of the tumor [1]. Although the most encouraging results, and the most recent interest, have been with positron emission tomography (PET) using 2-[ 18 F]fluoro-2-deoxyglucose (FDG) as the metabolic tracer [9,10,11,12,13,14], the potential role of single-photon-emitting tracers should not be ignored, particularly as PET is not a ubiquitous technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation